The influence of organizational culture, compensation and work discipline on performance employees the park and cleanliness unit (Tamsih) Panca Budi Medan - Nadiya Putri Indah; Hendra Utama (SEAN Institute, 2024)
Employees need better treatment from employers because they are the company's most valuable resource and the force behind the entire operation. This quantitative research aims to answer questions regarding employee performance as follows: (1) how organizational culture influences performance; (2) how compensation affects performance; and (3) how work discipline affects performance. The population of this study was active workers of the Panca Budi Medan Park and Cleanliness Unit (Tamsih), totaling 44 people, derived from the results of calculations carried out using the nonprobability sampling method. In order to collect information for this research, a questionnaire was sent to employees of the Tamsih Panca Budi Medan Unit. To find out what kind of respondents, data analysis uses tools including multiple linear regression, validity and reliability test, coefficient of determination test, t test, and F test. The data in this study was processed using SPSS 26for Windows. According to research, the impact of organizational culture on employee productivity is very small and insignificant. Partial compensation did not significantly improve productivity or profitability, according to the tests. Employee performance is greatly influenced by work discipline. There is a strong and beneficial relationship between employee performance and factors including organizational culture, compensation, and work discipline according to research.